Fabrication and characterization of collagen–hydroxyapatite-based composite scaffolds containing doxycycline via freeze-casting method for bone tissue engineering. (October 2018) - Semyari, Hossein; Salehi, Majid; Taleghani, Ferial; Ehterami, Arian; Bastami, Farshid; Jalayer, Toktam; Semyari, Hadis; Hamed Nabavi, Mir; Semyari, Hassan
In this study, hydroxyapatite nanoparticles containing 10% doxycycline, a structural isomer of tetracycline, was prepared by the co-precipitation method. It was added to collagen solution for the preparation of the scaffold with freeze-casting method in order to develop a composite scaffold with both antibacterial and osteoinductive properties for repairing bone defects. The scaffolds were evaluated regarding their morphology, porosity, degradation and cellular response. The scaffolds for further investigation were added in a rat calvaria defect model. The study showed that after eight weeks, the bone formation was relatively higher in the collagen/nano-hydroxyapatite/doxycycline group with completely filled defect when compared with other groups. Histopathological evaluation showed that the defect in the collagen/nano-hydroxyapatite/doxycycline group was fully replaced by the new bone and connective tissue. Our results provide evidence supporting the possible applicability of doxycycline-containing scaffolds for successful bone regeneration.